2014
DOI: 10.1180/claymin.2014.049.5.01
|View full text |Cite
|
Sign up to set email alerts
|

Element mobility during the formation of the Uzunisa-Ordu bentonite, NE Turkey, and potential applications

Abstract: Dacitic andesitic calc-alkaline lavas and their pyroclastic rocks of Upper Cretaceous age are widespread in the Ordu area, eastern Black Sea Coast of Turkey. Ca-bentonite and Ca/Nabentonite deposits with significant economic potential formed in the broader region. The mineralogy and geochemistry of these deposits were studied by X-ray diffraction (XRD), scanning electron microscopy (SEM) and chemical analyses. The parent rocks (PR) and bentonite samples were analysed for the major and trace element contents, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…The concentrations of these immobile elements and their ratios (Nb/Y‐Zr/TiO 2 ) vary systematically with differentiation in magma series, and as a result, different rock types and magma series may be distinguished (Winchester & Floyd, ). Some trace element discrimination diagrams (Nb/Y‐Zr/TiO 2 , Y‐Nb, Y + Ta‐Rb, and Y + Nb‐Rb) have been used as a means of determining the original rock types and the tectonic setting of the source volcanic rocks (Abedini, Calagari, & Akbari, ; Berkley & Baird, ; Christidis, ; Christidis & Huff, ; Floyd & Winchester, ; Hints, Kirimae, Somelar, Kallaste, & Kiipli, ; Huff, , ; Huff, Bergström, Kolata, Cingolani, & Astini, ; Huff et al, 1997; Kolarikova & Hanus, ; Muchangos, ; Özdamar et al, ; Pearce, ; Pearce & Cann, ; Pearce, Harris, & Tindle, ; Pellenard et al, ; Roberts & Merriman, ; Shervais, ; Spears, Kanaris‐Sotirios, Riley, & Krause, ; Teale & Spears, ; Winchester & Floyd, ; Wood, ). The determination of the type of parent rock in K‐bentonite occurrences may provide important information on ancient tectonic settings (Laviano & Mongelli, ).…”
Section: Source Magmas and Tectonic Settingsmentioning
confidence: 99%
“…The concentrations of these immobile elements and their ratios (Nb/Y‐Zr/TiO 2 ) vary systematically with differentiation in magma series, and as a result, different rock types and magma series may be distinguished (Winchester & Floyd, ). Some trace element discrimination diagrams (Nb/Y‐Zr/TiO 2 , Y‐Nb, Y + Ta‐Rb, and Y + Nb‐Rb) have been used as a means of determining the original rock types and the tectonic setting of the source volcanic rocks (Abedini, Calagari, & Akbari, ; Berkley & Baird, ; Christidis, ; Christidis & Huff, ; Floyd & Winchester, ; Hints, Kirimae, Somelar, Kallaste, & Kiipli, ; Huff, , ; Huff, Bergström, Kolata, Cingolani, & Astini, ; Huff et al, 1997; Kolarikova & Hanus, ; Muchangos, ; Özdamar et al, ; Pearce, ; Pearce & Cann, ; Pearce, Harris, & Tindle, ; Pellenard et al, ; Roberts & Merriman, ; Shervais, ; Spears, Kanaris‐Sotirios, Riley, & Krause, ; Teale & Spears, ; Winchester & Floyd, ; Wood, ). The determination of the type of parent rock in K‐bentonite occurrences may provide important information on ancient tectonic settings (Laviano & Mongelli, ).…”
Section: Source Magmas and Tectonic Settingsmentioning
confidence: 99%
“…The hydrological setting of an ash deposit influences leaching intensity and transport ( e.g. with strong leaching and downward flushing in ombrogenous paludal environments; Kiipli et al , 2010; Özdamar et al , 2014). In marine environments, ashes are subject to reworking and redistribution by currents, which can change the ratios of immobile elements as the separation of minerals of various densities is closely related to ambient environmental energy (Ver Straeten, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Other causes of the Eu anomaly in these alteration zones are the high activity of complex ligands, the highly acid pH of the hydrothermal solution and the increase in the ƒO 2 of the hydrothermal system, because Eu transfer is easy under such conditions (Sverjensky, 1984;Elderfield & Sholkovitz, 1987;Karakaya et al, 2012;Özdamar et al, 2014). However, due to very slight variations in Eu negative anomalies in the alteration zones, it can be concluded that pH changes were very small during the mation of these zones.…”
Section: Evolution Of Eu and Ce Anomalies In Alteration Zonesmentioning
confidence: 99%